Action document for inter-cultural and inter-ethnic dialogue - Shermuhamedova, . (Opción, 2019)
This article discusses the features of inter-cultural dialogue in the era of globalization and some tendencies of inter-ethnic relations in Uzbekistan via applying the methods of complex, comparative-historical study, and analysis; methods of empirical research – observation, description, comparison; theoretical methods – generalization, synthesis, and systematic analysis. As a result, the task of the intellectual elite is to clear this green road from weeds and, in the name of preserving peace, become a worthy example for the younger generation. In conclusion, humanity can avoid distrust, which is used as a basis for inciting hostility, hatred, and calls for violence.